2021
DOI: 10.1136/bmjopen-2020-045455
|View full text |Cite
|
Sign up to set email alerts
|

Integrating community health volunteers into non-communicable disease management among Syrian refugees in Jordan: a causal loop analysis

Abstract: ObjectivesGlobally, there is emerging evidence on the use of community health workers and volunteers in low-income and middle-income settings for the management of non-communicable diseases (NCDs), provision of out-of-clinic screening, linkage with health services, promotion of adherence, and counselling on lifestyle and dietary changes. Little guidance exists on the role of this workforce in supporting NCD care for refugees who lack access to continuous care in their host country. The goals of this work were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
“…CLDs were mostly seen as a means or a tool to examine feedback at play in public health issues. Some articles were explicit [28,32,33,40,43,44] while others implied this. Both Riley et al [43] and Parmar et al [40] labeled this as "causal loop analysis" and the resulting CLDs were a means to understand systems and potential "programming."…”
Section: Why Causal Loop Diagrams?mentioning
confidence: 99%
See 3 more Smart Citations